Penguatan Otot Lengan Sebagai Model Latihan Shooting 10 M Air Pistol Berbasis Koordinasi Meningkatkan Akurasi - Soemardiawan; Yundarwati, Susi; Marzuki, Ismail (Universitas Hamzanwadi, 2024)
NTB POPROV event January 17, 2022. The research method uses quantitative experiments, with a one group pretest posttest design. The entire population was used as a research sample, namely all PERBAKIN shooting athletes in NTB as many as 15 people. So this research is a population study research. The instrument uses (target paper). Data collection techniques using test methods, questionnaires or questionnaires, interviews, observations, rating scales or rating scales and documentation. The data analysis technique uses the T test assisted using the statistical product and Service Solution (SPSS 20) program. The average value of the results before being given arm muscle strengthening as a training model is 461.60 and after being given treatment with arm muscle strengthening as a training model 475.33, it means that the average mean value of arm muscle strengthening as a coordination-based 10 m air pistol shooting training model increases accuracy, there is an increase in shooting accuracy, the conclusion is an increase in shooting accuracy, meaning that arm muscle strengthening as a coordination-based 10 m air pistol shooting training model increases accuracy effectively and efficiently.